Information sharing in supply chain of agricultural products based on the Internet of Things. Issue 7 (8th August 2016) - Yan, Bo; Yan, Chang; Ke, Chenxu; Tan, Xingchao
Abstract : Purpose: – The Internet of Things (IoT) is one of the efficient ways to solve the problems on information sharing in the supply chain of agricultural products. The paper aims to discuss this issue. Design/methodology/approach: – In this paper, a scheme of information sharing in the supply chain of agricultural products is developed and the information of agricultural products is designed and described with Physical Markup Language. Findings: – In addition, the EPC Information Services (EPCIS) system of agricultural products is analyzed and designed, and the design of tracking and tracing of the agricultural supply chain based on the IoT is proposed. Meanwhile, EPCDS registration is discussed, and two methods of information inquiry are proposed, especially the processes of inquiries for the static and dynamic information based on Object Name Service are emphasized. Originality/value: – Once a food safety incident occurs, the model can be used for tracking, tracing, and monitoring so as to deal with related products and strengthen the quality and safety management of agricultural products.